Sofia the First storybook collection (Quezon City : Lampara Publishing House, 2016)
"Read about Sofia's first weeks as a princess, learn about her new family, discover the secret of her special amulet, and lots more!"--Cover.
Sofia's magic lesson
At head of title: Disney
Keywords: Children's stories